Pilar-pilar Kehidupan Beragama: Eksplorasi Perkembangan Jiwa pada Masa Anak-anak - Sudirman, Sudirman (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This study explores the spiritual development of children within the context of the pillars of religious life. The primary focus of the research is to understand how factors such as beliefs, religious practices, and spiritual experiences influence the emotional, social, and psychological development of children. The research approach employs qualitative methods, conducting in-depth interviews with 30 children aged 6-12 years from various religious backgrounds. The findings indicate that pillars of religious life such as religious rituals, moral values, and spiritual experiences significantly contribute to shaping the identity and psychological well-being of children. Children growing up in environments rich in religious life tend to have a deeper understanding of social and emotional values, as well as better abilities in managing emotions and forming interpersonal relationships. These discoveries provide valuable insights into the crucial role of religious life in the spiritual development of children, as well as its implications for educational practices and psychological interventions during this developmental stage. The study also underscores the need for a sensitive approach to religious diversity within the contexts of education and psychological support for children.